Discovery of cold ice in a new drilling site in the Eastern European Alps - Gabrielli P.; Barbante C.; Carturan L.; Cozzi G.; Dalla Fontana G.; Dinale R.; Dragà G.; Gabrieli J.; Kehrwald N.; Mair V.; Mikhalenko V.; Piffer G.; et al. (2012)
During autumn 2011 we extracted the first ice cores drilled to bedrock in the eastern European Alps from a new drilling site on the glacier Alto dell’Ortles (3859 m, South Tyrol, Italy). Direct ice core observations and englacial temperature measurements provide evidence of the concomitant presence of shallow temperate firn and deep cold ice layers (ice below the pressure melting point). To the best of our knowledge, this is the first cold ice observed within a glacier of the eastern European Alps. These ice layers probably represent a unique remnant from the colder climate occurring before ~1980 AD. We conclude that the glacier Alto dell’Ortles is now changing from a cold to a temperate state. The occurrence of cold ice layers in this glacier enhances the probability that a climatic and environmental record is fully preserved in the recovered ice cores.